Intrinsic connectivity patterns of striatal subfields predict individual dimensions of psychopathology and are associated with cholinergic and serotonergic neurotransmission in schizophrenia - He, Zhiqiu; He, Wenli; Chen, Zhiyi; Wei, Wei; Liu, Xiaojin; Dukart, Juergen; Li, Weidong; Baker, Justin T.; Holmes, Avram J.; Hoffstaedter, Felix; Nickl-Jockschat, Thomas; Derntl, Birgit; et al. (Neuropsychopharmacology, 2026)
Symptoms of schizophrenia may reflect different pathophysiological processes in the striatum, but the links between striatal subfield connectivity, symptom dimensions, and molecular architectures remain unclear. Using connectivity profiles from 12 striatal subfields to predict negative, positive, affective, and cognitive symptoms in schizophrenia, we identified consistent connectivity features through cross-validations and validated with leave-one-site-out analysis and an independent dataset. Feature importance scores for brain parcels linked through consistent connectivity features that predicted symptoms were spatially correlated with density maps of 19 receptors/transporters from prior molecular imaging in healthy populations using partial least squares. We found that the connectivity profiles of the rostral and ventral striatal subfields significantly predicted affective and cognitive symptoms, respectively, and these predictions were generalized to the independent sample. Feature importance scores for brain parcels connected to the ventral striatum (predicting cognitive symptoms) were spatially correlated with density maps of both the vesicular acetylcholine transporter and the serotonin 1 A receptor. By contrast, importance scores for parcels linked to rostral striatal connectivity (predicting affective symptoms) were specifically associated with the spatial distribution of the serotonin 1 A receptor. Here, we show specific striatal connectivity patterns related to symptom dimensions and indicate multiple neurotransmitter systems to underlie the reward-related disturbances in schizophrenia.
Gesehen am 11.02.2026